Incremental and decremental L- and M-cone-driven ERG responses: I. Square-wave pulse stimulation - Mckeefry, Declan; Kremers, Jan; Kommanapalli, Deepika; Challa, Naveen K.; Murray, Ian J.; Maguire, John; Parry, Neil R. A. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2014)
Electroretinograms (ERGs) elicited by transient, square-wave L- and M-cone isolating stimuli were recorded from human trichromatic (n=19) and dichromatic (n=4) observers. The stimuli were generated on a four primary LED stimulator and were equated in terms of cone modulation (cone contrast=0.11) and retinal illuminance (12,000 trolands). L- and M-cone isolated ERGs had waveforms similar to those observed for luminance responses. However, M-cone ERGs exhibited a phase reversal in their responses to onset and offset stimuli relative to the L-cone responses. This on-off response reversal was observed in trichromats but not dichromats. Simultaneous counterphase and inphase combinations of L- and M-cone isolating stimuli generated responses that reflected chromatic and luminance processing, respectively. We conclude that L- and M-cone specific ERGs provide a measure of how photoreceptors contribute to postreceptoral mechanisms.
EVALuna2:21214